Evaluating the Outcomes of the Canadian Watershed Research Consortium: A Research Contribution Framework Approach. - Petersen, Holly G.; Bergbusch, Nathanael T.; Hitchman, Katrina; Courtenay, Simon C. (Environmental Management, 2025)
Watersheds in Canada are being negatively affected by cumulative effects from anthropogenic activities. Canada has difficulty integrating cumulative effects into decision-making processes for both individual development projects and entire regions. The Canadian Watershed Research Consortium (CWRC) was a research program created by Canadian Water Network (CWN) that started in 2010 and formally ended in 2015. The purpose of the program was to develop cumulative effects assessment monitoring frameworks for six different watersheds across Canada. In this paper, we evaluated the impact of the CWRC on the capacity for decision-making in these watersheds using an adapted Research Contribution Framework as a methodological guideline. Data were collected through 14 semi-structured interviews and a document analysis of eight primary CWRC reports along with secondary information (57 journal publications). From the interviews, primary documents, and a scoring exercise, we found that the CWRC was successful in contributing to research uptake and research use, but that it may have fallen short in its overall research impact. We determined that some nodes (Muskoka, Northumberland Strait, Slave River) were able to institutionalize their cumulative effects monitoring frameworks in that an organization continues to collect data that will be used to inform policy and management. Factors contributing to research contribution included strong leadership and interest from governments and communities for maintaining at least some aspects of the monitoring program beyond the end of the Consortium. Important considerations for future research in this area include long-term follow-up and the relationship between cumulative effects monitoring and decisions made through environment assessments and watershed planning.